2021
DOI: 10.1001/jama.2021.7489
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response to 2-Dose SARS-CoV-2 mRNA Vaccine Series in Solid Organ Transplant Recipients

Abstract: This follow-up study measures the antibody response following the second dose of SARS-CoV-2 mRNA vaccine in recipients of solid organ transplants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

83
967
18
10

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 915 publications
(1,078 citation statements)
references
References 6 publications
83
967
18
10
Order By: Relevance
“…A recent study in JAMA looked at 658 organ transplant recipients and demonstrated a lower antibody response after both doses of the mRNA COVID-19 vaccines when compared to immunocompetent participants 21 . Similarly, early studies suggest that cancer patients do not mount the same antibody responses as healthy controls 22 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in JAMA looked at 658 organ transplant recipients and demonstrated a lower antibody response after both doses of the mRNA COVID-19 vaccines when compared to immunocompetent participants 21 . Similarly, early studies suggest that cancer patients do not mount the same antibody responses as healthy controls 22 .…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Initial reports indicate an impaired anti-SARS-CoV-2 antibody response among transplant recipients following mRNA vaccination, likely because of maintenance immunosuppression. 6,7,8,9 Whether kidney transplant recipients have low levels of virus-neutralizing antibody not detected by these assays or protective anti-SARS-CoV-2 T-cell immunity is currently unknown, and the critical question is whether the impaired antibody response corresponds to disease susceptibility. Here, we document 13 cases of COVD-19 in previously vaccinated kidney transplant recipients.…”
Section: To the Editormentioning
confidence: 99%
“…The potential for severe COVID-19 despite vaccination is a concern among transplant recipients, and these cases supplement recent reports that most transplant recipients do not develop a measurable antibody response to standard anti-SARS-CoV-2 mRNA vaccination schedules, although immunogenicity is higher once both doses are administered. 6,7,8,9 It is important to recognize that the efficacy of vaccination without the presence of detectable antibodies is unclear at present, as is the degree of protection afforded by the presence of a detectable anti-spike antibody response. Results from this single-center summary must be reviewed with consideration to the dynamic changes of COVID-19 infections, in the context of community disease transmission and vaccination rates.…”
Section: To the Editormentioning
confidence: 99%
“…Nach der zweiten Impfung wurde bei Patient*innen mit soliden Tumoren eine Serokonversion von 95 % erreicht [ 8 ]. Niedrigere Serokonversionsraten nach einmaliger Impfung wurden auch bei Z. n. Organtransplantation beobachtet [ 2 ]. Diese Daten deuten darauf hin, dass bei Verwendung eines mRNA-Impfstoffs die zweite Schutzimpfung bei Krebspatient*innen zeitnah, d. h. nach 3 bzw.…”
Section: Empfehlungen Zur Schutzimpfung Gegen Covid-19 Bei Krebspatient*innenunclassified